Peran Pendidikan Formal dalam Meningkatkan Mobilitas Sosial Siswa dari Keluarga Miskin: Studi Kualitatif di SMP Negeri 5 Sangatta Utara - Avryn Wella Saputri; Yunia Cahya Laila; Muhammad Yasin (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2025)
This study aims to analyze in-depth the role of formal education in facilitating and enhancing the social mobility of students from low socioeconomic backgrounds at SMP Negeri 5 Sangatta Utara. Social mobility is understood not only as an increase in economic status but also as an increase in students' cultural capital and life aspirations. Using a qualitative case study approach, data were collected through in-depth interviews with the principal, teachers, students, and parent representatives, as well as participant observation of school activities. The study results indicate that schools play a significant role as agents actively counteracting students' cultural capital deficits by providing an environment that encourages the development of non-academic skills, such as leadership and public speaking. Key internal factors supporting this role are teachers' pedagogical consistency and innovative school leadership in integrating professional values. External driving factors include the existence of an alumni network that serves as inspiring mentors and provides psychological support from the majority of parents. It is concluded that a school's effectiveness in enhancing social mobility depends largely on its ability to bridge the gap between instilled values ​​and the socioeconomic realities of families through structured partnership programs.